Improving the potential for organ donation in an inner city Muslim American community: the impact of a religious educational intervention. (24th December 2013) - Hafzalah, Mina; Azzam, Ruba; Testa, Giuliano; Hoehn, K. Sarah
Abstract Objective We aimed to assess the willingness of Muslim Americans to be potential organ donors, to describe potential religious barriers to organ donation, and to evaluate the efficacy of a brief religious educational intervention. Methods Face‐to‐face survey with English‐, Arabic‐, and Urdu‐speaking Muslim American adults in places of worship and gatherings. The two‐part survey included questions about demographics and organ donation. A brief educational intervention followed, which included an explanation of organ donation, along with the evidence for Islam's support for organ donation. After this intervention, the questions about organ donation and brain death were repeated. Results The response rate was 81% (231 of 285). Fifty percent of the respondents would donate their organs. Twenty‐five percent changed their opinion and accepted the idea of being donors after the educational intervention. Lack of awareness of the support of Islam to organ donation and fear of disfigurement were the most common barriers cited. Conclusion Muslim Americans are less likely than Caucasian Americans to be organ donors, and the perceived lack of support from Islam for organ donation is a factor. The effectiveness of our brief religious education intervention suggests that further education may improve organ donation rates among the Muslim community.